2002
DOI: 10.1093/nar/gkf532
|View full text |Cite
|
Sign up to set email alerts
|

Human Mcm proteins at a replication origin during the G1 to S phase transition

Abstract: Previous work with yeast cells and with Xenopus egg extracts had shown that eukaryotic pre-replication complexes assemble on chromatin in a step-wise manner whereby specific loading factors promote the recruitment of essential Mcm proteins at pre-bound origin recognition complexes (ORC with proteins Orc1p-Orc6p). While the order of assembly--Mcm binding follows ORC binding--seems to be conserved in cycling mammalian cells in culture, it has not been determined whether mammalian Mcm proteins associate with ORC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
48
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 68 publications
10
48
0
Order By: Relevance
“…ChIP experiments with HeLa cells were performed essentially as described previously (60). Briefly, 1 ϫ 10 8 HeLa cells were washed with phosphate-buffered saline (PBS) and treated with 1% formaldehyde in prewarmed medium for 4 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ChIP experiments with HeLa cells were performed essentially as described previously (60). Briefly, 1 ϫ 10 8 HeLa cells were washed with phosphate-buffered saline (PBS) and treated with 1% formaldehyde in prewarmed medium for 4 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…2 and 3) suggested that in their native chromosomal context, these replicators are likely licensed during G 1 phase to initiate replication. This prediction was tested by measuring Orc2p enrichment at the potential origins ori6 and ori9 in their native chromosomal contexts in ChIP assays relative to preimmune control precipitates and the input DNA (35,60). In initial experiments with asynchronously proliferating HeLa cells, we found that the origin sequence (UPR) (Fig.…”
mentioning
confidence: 99%
“…PCR reactions were performed for 45 cycles with standard settings as recommended by the manufacturer. Sequences and conditions for each primer pair are exactly as those described by Schaarschmidt et al (29). Standard DNA samples were diluted from 30, 3, and 0.3 ng up to 30 pg.…”
Section: Methodsmentioning
confidence: 99%
“…This origin is located in the region between the two active human genes PRKDC and MCM4. It includes the site where ORC is bound and where the assembly of a prereplication complex is initiated (29,34).…”
Section: Geminin and Cdt1 On Chromatin In Proliferating Helamentioning
confidence: 99%
“…The LB2 gene origin of replication (31) and the origin located in the UPR of the MCM4 gene (32) were utilized in this study, and PCR analysis was performed from the areas shown ( Figs. 1 and 2).…”
Section: Methodsmentioning
confidence: 99%